PERTARUNGAN SYARIAH DI RUANG WACANA: ANALISIS KRITIS PANDANGAN KEAGAMAAN PADA TEMPO DAN SUARA HIDAYATULLAH - Dadang S. Anshori (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
; "> This paper aims to describe the different discourses in syariah practices as described in mass media. The method used in this study is qualitative design based on Fowler’s critical discourse analysis. The sources of the data are the use of language of syariah practices from Tempo magazine and Suara Hidayatullah. Some important findings found from Tempo magazine include words such as discriminative, inconstitusional, autoritarianism, collision, enticing Islam constituent, minority group, not applicable, children’s right protection, traumatic, stigma, violent act, and repressive. Meanwhile, word choices found from Suara Hidayatullah were terror, criminal acts, careless conclusion, cynical, simplistic, unprofessional, defamation and anti-Islam. From both choices of words, Tempo and Suara Hidayatullah show explicitand implicit attitude in which the first show anti-syariah with its pluralism democracy,while the latter is pro-syariah which is based on Islam ideology.